Construction of the annual macrocycle of short-distance runners at the stage of in-depth specialization - Kozhedub, M. S.; Godun, D.; Vrublevsky, E. P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to improving the sports training of sprinters aged 15-17 years based on the analysis of the dynamics of their training loads and the ratio of work of various directions in the annual cycle.